Behind the Veil of Blue Ecolabelling: Dismantling the Juxtaposition of International Regulations on Sustainable Oceans - Woods, Jonathan; Meliala, Aurora Jillena (Padjadjaran Journal of International Law, 2023)
Ecolabelling was introduced as an alternative consumer-facing mechanism in the market to combat certain threats against the environment and to promote sustainable usage of its components. More importantly in the case of Indonesia as a maritime country, fishery ecolabels can be used to build sustainability to its marine environment which can be vital for its economy in the future. To this end, this article constructs an exposition of ecolabels from a legal perspective in the international and local contexts that is still absent in Indonesia’s legal research. This study employs normative legal research methodology in its data collecting and analysis. The article in its analysis will argue that while the international standards provided for blue ecolabels are robust, its genuine implementation can only be realized in the domestic scene, where local aspects can be considered. This research in the end finds that an ecolabelling of fisheries in Indonesia is urgently needed, concludes that ecolabelling in fisheries can help the state in realizing its international commitments, and recommends its urgent creation in the national scene.